THE POWER OF THE TRUTHFUL: SATYA IN THE NONVIOLENCE OF GANDHI AND HAVEL - van Goelst Meijer, Saskia (International journal on world peace, 2015)
Conflicting global narratives on good or right living, based on conflicting truth-claims, can often lead to violence. We can find examples in religious, ethnic, or ideological conflicts that confirm this. One of the central elements in the practice of nonviolence is that of satya, a Sanskrit term best translated as "truth." Satya points to a very specific conception of truth and that by examining the lives and work of both Mohandas Gandhi and Václav Havel, satya as a practice of complexity handling is explored. In a globalizing world in which people have no choice but to position themselves in the multiplicity of narratives, developing skills of handling complexity are crucial. This paper argues that the theory and practice of nonviolence holds clues for how to do this. I use the term nonviolence here not only to point to the absence of violence in solving problems, but as a coherent set of ideas and practices that provide a framework for understanding (social) reality.